Emergence of Internet Services and Personal Accounts: A study conducted amongst people in Bilaspur, Chhattisgarh - Prasad Singhraul, Dr. Budheshwar; Kumari Soni, (Ms.) Vanita (IJRDO - Journal of Business Management, 2017)
In today’s world, nobody can be independent and require others for their survival. People can afford huge money but cannot produce each and every product by themselves and so they need to buy products from the others and thus, is the need for transactions. These transactions usually are done at the shops or markets and require cash money for doing transactions, but with the development of online facilities, transactions are done through online system or internet services and these can be done by sitting at one place in any part of the world by gaining access to internet. These online purchases / deals / transfers / banking / bidding / buying / selling etc. could be done by any person in the world 24X7 and people can save these transactions details as per their requirement and can maintain their records / personal accounts. These have decreased the burden on the banking system. For the purpose of the study, data was collected from 325 respondents based on self structured questionnaire. The study concluded that the individuals are able to maintain their personal accounts and keep tracks of personal accounts using internet services with ease, which are greatly influenced by the age, gender, occupation and income of the respondents.